PERAN GURU DALAM UPAYA MENINGKATKAN HIGHER ORDER THINKING MELALUI GAYA MENGAJAR GUIDED-DISCOVERY PADA PEMBELAJARAN PENDIDIKAN JASMANI - Mesa Rahmi Stephani (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2016)
This article is presented through a study of literature to explain the association of guided-discovery teaching styles with an effort to increase higher-order thinking that can also be said to be the level of critical thinking. In the guided-discovery teaching style, the teacher guides the student into discovery learning situations on movement problem. Movement problem solved is based on discovery results, from the process of knowing, understanding, applying, analyzing, synthesizing, and evaluating.Keywords: Guided-Discovery Teaching Style Higher-Order Thinking.         ABSTRAKArtikel ini disajikan melalui kajian teoritis yang berupaya memaparkan keterkaitan gaya mengajar guided-discovery dengan upaya peningkatan higher-order thinking yang dapat pula dikatakan tingkat berpikir kritis. Pada gaya mengajar guided-discovery, guru membimbing siswa ke dalam situasi pembelajaran discovery tentang pemecahan masalah gerak. Pemecahan masalah gerak dilakukan berdasarkan hasil discovery, mulai dari proses mengetahui, memahami, menerapkan, menganalisis, mensintesis, dan mengevaluasi.Kata kunci: Gaya Mengajar Guided-Discovery Higher-Order Thinking.